ENHANCING ENGAGEMENT IN QRIS ADOPTION: THE IMPACT OF EASE OF USE ON USAGE DECISIONS WITH TRUST AS A MEDIATING VARIABLE AMONG USERS IN JAMBI PROVINCE - Arvelita, Alya Diandra; Yacob, Syahmardi; Sari, Novita (Journal of Business Studies and Management Review, 2025)
This study examines the impact of ease of use on QRIS usage decisions, with trust as a mediating variable among users in Jambi Province. Employing a quantitative approach with a survey method, data were collected from 100 respondents and analyzed using Partial Least Squares (PLS). The findings reveal that ease of use has a positive and significant effect on user trust—individuals who perceive QRIS as easy to learn and operate tend to exhibit higher levels of trust. However, ease of use does not directly influence usage decisions. Instead, trust plays a crucial mediating role, significantly affecting users' decisions to adopt QRIS. These results highlight the necessity of enhancing usability and fostering trust to drive broader adoption.nThis study contributes to the existing literature by providing empirical evidence on the mediating role of trust in the relationship between ease of use and usage decisions in the context of digital payment adoption. The findings offer practical implications for policymakers, financial institutions, and QRIS developers in designing strategies that improve user experience and build trust to accelerate QRIS adoption. By addressing key factors influencing user decisions, this research supports the development of more effective digital payment ecosystems in Indonesia.